2019 XV Workshop De Visão Computacional (WVC) 2019
DOI: 10.1109/wvc.2019.8876924
|View full text |Cite
|
Sign up to set email alerts
|

Automation of Waste Sorting with Deep Learning

Abstract: Gostaria de expressar a minha sincera gratidão ao professor Jaime Cardoso, pela disponibilidade, e pelas suas ideias que elevaram este projeto. Também com a ajuda da professora Ana Rebelo, melhorei como estudante e engenheiro. Uma palavra ao INESC TEC e ao membros do CTM por me terem acolhido e ajudado sempre que necessário. Porque esta tese é também fruto dos últimos cinco anos, gostaria de agradecer ao professor Armando Sousa pelas experiências fantasticas e enriquecedoras na Universidade Júnior, Mostra UP e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…The network was trained for six objects classes (such as glass, cardboard, paper, metal, organic and plastic waste). Sousa et al [19] proposed a hierarchical DL model for waste classification and detection in food trays. The proposed 2 phase method maintains the benefits of current object detectors (as Faster RCNN) and permits the classification process to be assisted in high resolution bounding box.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The network was trained for six objects classes (such as glass, cardboard, paper, metal, organic and plastic waste). Sousa et al [19] proposed a hierarchical DL model for waste classification and detection in food trays. The proposed 2 phase method maintains the benefits of current object detectors (as Faster RCNN) and permits the classification process to be assisted in high resolution bounding box.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for those new optical sorting technologies for which interest is currently gaining momentum, VIS-sorting combined with AI-based image processing technologies represents one such technology [201][202][203]. There are already commercial robotic sorting solutions existing on the market [204,205].…”
Section: Exploring Future Perspectivesmentioning
confidence: 99%
“…But, the accuracy was not effective. Sousa et al (11) suggested a hierarchical Faster Region-based CNN (FR-CNN) for identifying and classifying the wastage in food trays. Also, a novel dataset called labeled wastage in the wild was collected and annotated for classification.…”
Section: Literature Surveymentioning
confidence: 99%